ANALISIS TINGKAT KESELAMATAN RUAS JALAN DITINJAU DARI ASPEK KELENGKAPAN INFRASTRUKTUR (STUDI KASUS : JL RAYA SAMBIGEDE, KEC. SUMBERPUCUNG, KAB. MALANG) - Yustina, Yustina Nimun; M. Sa'dillah; Pamela Dinar Rahma; Yustina , Yustina Nimun (Universitas Islam Balitar Blitar, 2025)
The absence of traffic equipment facilities is the primary cause of accidents in the current field. Following a review of accident data, road equipment, and user behaviour, suggestions are made for the enhancement and installation of facilities, such as speed limit signs, warning signs, fading road markings, and broken supublic street lighting on Sambigede Highway. This research sought to ascertain the degree of road safety and the actions required to improve it. adding street lighting equipment, warning lights, speed restriction signs, and signage for regions that are prone to accidents.